Slang Words in Da'wah by Popular Preachers on Youtube - Syam, Muhammad Taufiq; Tike, Arifuddin; Tajibu, Kamaluddin; Nurhikmah, Nurhikmah (Jurnal Dakwah Risalah, 2023)
Da'wah on Youtube is a part of the process of distributing da'wah messages through social media. The preachers use slang words in da’wah as a way to attract attention to audience, as personal identity, and to meet the standards of uses and gratification of the audience, even though they have to ignore the Qaulan ethics in da'wah. This study uses a qualitative descriptive method to describe several conditions, situations and phenomena of da'wah on Youtube. Sources of research data are documentation, online surveys and in-depth interviews related to the phenomenon of using slang words in da'wah. Based on the research results, it was found that the use of slang words in da'wah aims to attract the attention of the audience, establish the personal identity, and meet the standards of uses and gratification based on cognitive, affective, and behavioral levels of the audience. A positive reconstruction is needed to minimize the occurrence of distortions in the use of slang words and the Qaulan ethics in da’wah.